Functional Multiplicity of an Insect Cytokine Family Assists Defense Against Environmental Stress - Shears, Stephen B.; Hayakawa, Yoichi (Frontiers in Physiology, 2019)
The widespread distribution of insects over many ecological niches owes much to evolution of multiple mechanisms to defend against environmental stress, especially because their ectothermic nature and small body size render them particularly susceptible to extremes in temperature and water availability. In this review, we will summarize the latest information describing a single, multifunctional cytokine family that is deployed by six orders of insect species to combat a diverse variety of environmental stresses. The originating member of this peptide family was identified in Mythimna (formerly called Pseudaletia) separata armyworm; the cytokine was named growth-blocking peptide (GBP), reflecting its actions in combating parasitic invasion. The peptide’s name has been retained, though the list of its regulatory activities has greatly expanded. All members of this family are small peptides, 19–25 amino acid residues, whose major source is fat body. They are now known to regulate embryonic morphogenesis, larval growth rates, feeding activities, immune responses, nutrition, and aging. In this review, we will describe recent developments in our understanding of the mechanisms of action of the GBP family, but we will also highlight remaining gaps in our knowledge.